5-a-Side Game as a Tool for the Coach in Soccer Training. Issue 5 (October 2021) - Branquinho, Luís; Ferraz, Ricardo; Marques, Mário C.
Abstract : ABSTRACT: Physical outputs in soccer training can be influenced by the interaction of several variables during the performance of different small side games (SSGs) formats. For this reason, it is relevant to understand how the manipulation of variables such as training method, exercise duration, number of repetitions, or recovery time affect the training loads and the performance. The main aim of this work was to provide coaches with relevant theoretical aspects and examples of practical applications to use from the specific format of 5-a-side SSG. To search for relevant publications and ensure the quality of articles, the search strategy used comprised specific search terms based on the research theme. The results showed that, during the 5-a-side game format, the choice of the training method (i.e., continuous or fractionated) and the manipulation of the related variables (e.g., number of players and game format) are fundamental for the management of the training load. Therefore, the manipulation of the variables using 5-a-side format translates into significant variations in the training load, and in the likely improvement of the different domains of soccer training (physiological, technical, and tactical), thus evidencing several benefits in the use of this game format. In addition, practical examples of 5-a-side exercises are used based on the theoretical considerations described.